The Application of Computer Information Technology in Network Security under the Background of Big Data - Zhang, Junshan (Journal of Theory and Practice of Management Science, 2025)
With the development of technology, the use of electronic computers and other cutting-edge facilities is becoming increasingly common, which has profoundly influenced people's daily lives and changed their way of thinking.However, due to the rise of big data, it is particularly necessary to improve the reliability of computer information systems. Therefore, we should double our attention and strengthen the application of network security technology to improve the reliability and operability of computer information systems.In response to this, we will focus on how to use big data to improve Internet security and give effective suggestions.